Second International Conference and Workshop on Interventional Radiology 2023, Dhaka, Bangladesh: Advancements, Achievements, and Challenges - Datta, Anindita; Bhowmik, Bishwajit; Alam, Syed Zoherul; Islam, Md Tariqul; Sultana, Syeda Naheed (Journal of Clinical Interventional Radiology ISVIR, 2024)
Interventional radiology, which combines diagnostic and therapeutic approaches to address and treat a variety of medical diseases, has emerged as an expeditiously developing area at the confluence of radiology and minimally invasive procedures. The authors provide a general overview of the Bangladesh Society of Vascular and Interventional Radiology (BSVIR), including its goals, contributions, and effect on the Bangladeshi healthcare sector. The second interventional radiology conference was held in Dhaka and was organized by the Bangladesh Society of Radiology and Imaging, and BSVIR, in alliance with the Indian Society of Vascular and Interventional Radiology. This allowed the exchange of ideas and innovations as well as a discussion of recent advances in this dynamic field. This manuscript also highlights the key points, emerging trends, and scientific sessions that were presented at the conference.
Keywords: interventional radiology; BSVIR; interventional radiology conference Dhaka 2023